Horizontal Wavenumber Spectra Across the Middle Atmosphere From Airborne Lidar Observations During the 2019 Southern Hemispheric SSW - Knobloch, Stefanie; Dörnbrack, Andreas; Kaifler, Bernd; Rapp, Markus (Geophysical Research Letters, 2023)
Horizontal wavenumber spectra across the middle atmosphere are investigated based on density measurements with the Airborne Lidar for Middle Atmosphere research (ALIMA) in the vicinity of the Southern Andes, the Drake passage and the Antarctic peninsula in September 2019. The probed horizontal scales range from 2000 to 25 km. Spectral slopes are close to k−5/3 in the stratosphere and get shallower for horizontal wavelengths <200 km in the mesosphere. The spectral slopes are shown to be statistically robust with the presented number of flight legs despite the unknown orientation of true wave vectors relative to the flight track using synthetic data and a Monte Carlo approach. The largest spectral amplitudes are found over the ocean rather than over topography. The 2019 sudden stratospheric warming caused a critical level for MWs and a reduction of spectral amplitudes at horizontal wavelengths of about 200 km in the mesosphere.